Students’ Reading Anxiety and Comprehension in An Indonesian Madrasah: A Correlational Case Study - Sakinah, Nuri Oktaviani; Basri, Hasan (PANYONARA: Journal of English Education, 2025)
The capacity to extract information from written texts and exhibit knowledge or comprehension of that information is known as reading comprehension. The word "anxiety" is vague and difficult to define and describe in a straightforward statement. Feelings of unease, dissatisfaction, self-doubt, apprehension, or worry are frequently linked to anxiety. The objective of this research is to investigate the correlation between studentâ€™s anxiety and reading comprehension. This research employs quantitative correlational study, with 54 samples of students. The analysis method uses adapted FLRAS and reading comprehension test. Students’ anxiety levels and their reading comprehension achievement had negative association of -0.407, according to the research’s statistical analysis. This correlation’s N.Sig value of.002 (less than 0.05) indicated that it was also statistically significant. As a result, the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted.